The quest of tourism and overall well-being: the developing economy of Pakistan. Issue 2 (13th June 2020) - Khan, Asif; Bibi, Sughra; Lyu, Jiaying; Alam, Mohammad; Khan, Muhammad Mussa; Nurunnabi, Mohammad
Abstract : Purpose: This study aims to examine the causal relationship between tourism and overall well-being. The main objective of this research is to inform the policymakers that tourism can play a vital role in shaping the overall well-being in the developing economies. Design/methodology/approach: This investigation used several time series techniques and procedures that include bounds test and autoregressive distributed lag mechanism to analyze the relationship between tourism and overall well-being in Pakistan by using time series data for the period 1980-2016. Findings: The findings suggest a significant positive relationship between tourism and overall well-being both in the short and long run. The authors find that tourism and overall well-being affect each other positively. Practical implications: This research indicates that policymakers and government can improve the overall well-being through tourism development. However, tourism policies and long-term planning should be focused on sustainable developments for achieving long-term goals. Besides, special incentives should be provided to the private sector for tourism development. Originality/value: To the best of the authors' knowledge, this is the first investigation that examines the causal relationships between tourism and overall well-being through objective indicators in a developing economy. This study fills the immense literature gap and provides new directions to scholars to investigate the mentioned relationship through objective indicators.